Consumer Ethnocentrism and Willingness to Buy Foreign Products in Emerging Markets: Evidence from Turkey and Colombia. Issue 2 (2nd April 2020) - Zeren, Deniz; Kara, Ali; Arango Gil, Alejandro
Abstract: Consumer ethnocentrism (CE) has been a popular research topic in international marketing. However, limited CE research is available from the emerging markets. Heightened concerns about globalization and increased political support for restricting international trade around the world increases the importance of updated empirical findings on consumer ethnocentric behavior. Hence, the purpose of this empirical study is to examine consumer ethnocentrism and consumer willingness to buy foreign products in two emerging markets: Turkey and Colombia. Data was collected using online surveys from subjects in Turkey and Colombia. Results show that CE inversely influenced consumers' willingness to buy foreign products in both countries.